Firms Left Behind: Emigration and Firm Productivity - Yvonne Giesing; Nadzeya Laurentsyeva (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper establishes a causal link between the emigration of skilled workers and firm performance in source countries. Using firm-level panel data from ten Eastern European countries, we show that the emigration of skilled workers lowers firm total factor productivity. We exploit time, country, and industry differences in the opening of EU labor markets from 2004 to 2014 as a source of exogenous variation in the emigration rates from new EU member states. We argue that a potential channel behind this effect relates to the reduction in firm-specific human capital due to a higher worker turnover.
Keywords: O15; D24; F22; J24; 330; migration; firm productivity; human capital; EU enlargement